2016
DOI: 10.3892/mmr.2016.5134
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of microRNA-337 promotes the proliferation of endometrial carcinoma cells via targeting PTEN

Abstract: Abstract. Endometrial carcinoma (EC) is a common malignancy in females. MicroRNAs (miRs) are a class of non-coding RNA that regulate a wide variety of cellular processes, and are important in the development of multiple types of malignancy. In the present study, cancerous and adjacent non-cancerous normal tissue samples were collected from 24 patients diagnosed with EC. Reverse transcription quantitative polymerase chain reaction was performed on the tissue samples to determine the expression levels of six can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Our literature review identified 30 articles studying the expression pattern of miR in neoplastic endometrial tissue compared to in benign and/or hyperplastic tissues [13,14,23,24,25,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52]. The studies included an average of 45 endometrial tumor samples (minimum 7, maximum 141), with well-defined histological types for 15 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review identified 30 articles studying the expression pattern of miR in neoplastic endometrial tissue compared to in benign and/or hyperplastic tissues [13,14,23,24,25,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52]. The studies included an average of 45 endometrial tumor samples (minimum 7, maximum 141), with well-defined histological types for 15 studies.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that miRs can act as oncogenes or tumor suppressors by targeting cancer-related genes in the development and carcinogenesis of EC and might be used as a diagnostic biomarker for human cancers [911]. For example, miR-337 was oncogenic and upregulated in EC cells and could markedly promote proliferation and inhibit apoptosis by suppressing PTEN expression [12]. miR-625 was reported to exhibit downregulation in EC and increase cell proliferation and invasion by targeting Sox2 [13].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Liu and Chen [41,42] discovered that NR4A1 could be a critical general regulator in the induction of T cell dysfunction and inhibit NR4A, thus, NR4A1 was seen as promising in cancer immunotherapy. The prognostic DEmiRNA, hsa-miR-337-3p targeting one DEmRNA (AMOT, a witnessed oncogene in OSCC [43]), has been implicated to target AMOT, HOXB7 [44], MMP-14 [45], PTEN [46] and acted as a tumor suppressor through sponging oncogene. Loss of miR-337-3p expression was associated with the development of cancer [47].…”
Section: Discussionmentioning
confidence: 99%